Integration of mobile technologies into the educational process - Guskov V. V. (Relevant lines of scientific research: theory and practice, 2025)
The article covers the use of computer technologies in education. Mobile technologies are considered as a tool that simplifies the development of an intellectual environment with constantly changing resources.
Keywords: образование; мобильные технологии; компьютерные технологии; виртуальная образовательная среда; education; computer technologies; mobile technologies; virtual educational environment